INTERACTIVE EDUCATION OF GIFTED STUDENTS - REŠKOVÁ, Martina; HOMOLKOVÁ, Veronika (Trends in education, 2013)
The topic of this article is interactive education of talented individuals in the pedagogically-educated facility environment. The interactive form of talented individuals focuses, above all, on students activation in the tuition through intensive senses utilization, concentration on tasks improvement as well as it significantly influences the overall individual's motivation for activities.
Keywords: talent; types of talent; interactive education; interactive whiteboards